The Effectiveness of Consumer Complaint Services in Improving Customer Satisfaction Mediated by Customer Experience: an Empirical Study at PT Jasa Raharja - Aldino Salam; Fahrul Riza; Endi Sarwoko (Eduvest - Journal of Universal Studies, 2025)
Customer satisfaction is a critical factor in ensuring business sustainability, particularly in service industries that rely on customer interaction. In the context of complaint handling, the effectiveness of consumer complaint services plays a key role in shaping customer experience, which in turn influences satisfaction levels. PT Jasa Raharja, as a state-owned social insurance company, faces challenges in improving the quality of its complaint services, with a significant increase in the number of complaints each year. However, surveys reveal persistent issues such as slow response times, lack of concrete solutions, and limited accessibility—factors that negatively impact both customer experience and satisfaction. This study aims to identify complaint service indicators that influence customer experience and satisfaction, and to explore the mediating role of customer experience in this relationship. A quantitative approach using Partial Least Squares – Structural Equation Modeling (PLS-SEM) and mediation analysis was employed. The findings indicate that complaint services significantly affect both customer experience and satisfaction. Furthermore, customer experience significantly mediates the relationship between complaint services and customer satisfaction. These results highlight the importance of enhancing complaint service quality to foster positive customer experiences and improve overall satisfaction.